2016
DOI: 10.1128/jb.00963-15
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudomonas aeruginosa PAO1 Two-Component Regulator CarSR Regulates Calcium Homeostasis and Calcium-Induced Virulence Factor Production through Its Regulatory Targets CarO and CarP

Abstract: Pseudomonas aeruginosa is an opportunistic human pathogen that causes severe, life-threatening infections in patients with cystic fibrosis (CF), endocarditis, wounds, or artificial implants. During CF pulmonary infections, P. aeruginosa often encounters environments where the levels of calcium (Ca 2؉ ) are elevated. Previously, we showed that P. aeruginosa responds to externally added Ca 2؉ through enhanced biofilm formation, increased production of several secreted virulence factors, and by developing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 75 publications
(100 reference statements)
3
60
0
4
Order By: Relevance
“…CarSR in Vibrio cholerae is induced by Ca 2ϩ and negatively regulates biofilm formation and exopolysaccharide production (31). In P. aeruginosa PAO1, the TCS orthologous to CvsSR, BqsSR, is also induced by Ca 2ϩ and regulates the cytosolic Ca 2ϩ concentration (38). However, to our knowledge, CvsSR is the first Ca 2ϩ -induced TCS characterized in a hemibiotrophic plant-pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…CarSR in Vibrio cholerae is induced by Ca 2ϩ and negatively regulates biofilm formation and exopolysaccharide production (31). In P. aeruginosa PAO1, the TCS orthologous to CvsSR, BqsSR, is also induced by Ca 2ϩ and regulates the cytosolic Ca 2ϩ concentration (38). However, to our knowledge, CvsSR is the first Ca 2ϩ -induced TCS characterized in a hemibiotrophic plant-pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 92%
“…The TCS orthologous to CvsSR in Pseudomonas aeruginosa is induced by Ca 2ϩ (38). To test for induction of cvsS and cvsR by Ca 2ϩ , we designed a luciferase promoter gene construct that included 400 bp upstream of PSPTO_3383 (P cvsSR ), which included a previously mapped transcriptional start site for PSPTO_3383, and introduced it into WT, ΔcvsS, and ΔcvsR strains of P. syringae pv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest activity of 0.813 U/ml was obtained from 6 mM CaCl2.2H2O (Figure 3). Calcium is an essential element in cell signalling and is required as a cofactor for many enzymes (Guragain et al, 2016). However, a high concentration of calcium ions could be toxic to the cells and decrease growth (Guragain et al, 2016).…”
Section: Effect Of Different Camentioning
confidence: 99%
“…Calcium is an essential element in cell signalling and is required as a cofactor for many enzymes (Guragain et al, 2016). However, a high concentration of calcium ions could be toxic to the cells and decrease growth (Guragain et al, 2016). Other research conducted by Vasiee et al (2016) reported that optimal enzyme production conditions from Bacillus cereus the Submerged Fermentation Method in Palm Oil Mill Effluent incubated at 37C for 48 h were achieved with 24.23 mM MgCl2 together with a coriander seed extract (CSE)/yeast extract ratio of 16.9 (m/m) and a concentration of 2.37 g/L of olive oil.…”
Section: Effect Of Different Camentioning
confidence: 99%